Perbedaan Sistem Pelayanan Medis Dokter dengan Standar INA-CBGs (Studi Kualitatif Pasien Ketuban Pecah Dini di RS X) - Faik Agiwahyuanto (Dian Nuswantoro Semarang, 2017)
BPJS (Social Insurance Administration Agency) Health will pay the irst-level health facilities with capitation. For advanced level referral health facilities, Health BPJS pay package system Indonesia Case Base Groups (INA-CBGs). INA-CBGs system is a classiication of patient care episode that designed to create classes that are relatively homogeneous in terms of resources used and contained patients with similar clinical characteristics. Hospitals will receive payments based on the average amount spent on a group diagnosis.This was qualitative study. The informants were 6, devided into 3 person as main informants and 3 triangulation informant, they were selected by snowball sampling techniques. The indepth interview data was transcripted in March 2016 then analyzed by the content analysis.Diferent diagnoses and medical procedures for standard medical services of doctors in hospitals with INA-CBGs standards, for example, premature infarction (KPD) should be performed by Sectio Caesarea (SC) up to 6 hours while INA-CBGs for early SC delivery within 24 hours. The hospital needs to increase the number of coding teams, hospital veriiers, and BPJS officer, and monitor and evaluate doctors, medical records, and hospital internal veriiers by clinical micro system under SIM-RS and coding units.Keywords: medical diagnosis, INA-CBGs, Premature rupture of membranes.